2016
DOI: 10.1016/j.eja.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Organic and mineral fertilization management improvements to a double-annual cropping system under humid Mediterranean conditions

Abstract: The efficient use by crops of nitrogen from manures is an agronomic and environmental issue, mainly in double-annual forage cropping systems linked to livestock production. A six-year trial was conducted for a biennial rotation of four forage crops: oat-sorghum (first year) and ryegrass-maize (second year) in a humid Mediterranean area. Ten fertilization treatments were introduced: a control (without N); two minerals equivalent to 250 kg N ha-1 yr-1 applied at sowing or as sidedressing; dairy cattle manure at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…The application of organic residues increases microbial activity; soil pH; soil test levels of P, K, Ca, Mg, Zn, and Cu; C content; water retention; the aggregation of soil; and carbon sequestration [9,10]. Animal manures impact the nutrient recovery of crops due to their more variable compositions and differential reaction rates compared to mineral fertilizers [11][12][13][14]. Nutrient recovery depends on a soil's capacity to supply nutrients and a plant's ability to acquire, transport, and remobilize nutrients [15].…”
Section: Introductionmentioning
confidence: 99%
“…The application of organic residues increases microbial activity; soil pH; soil test levels of P, K, Ca, Mg, Zn, and Cu; C content; water retention; the aggregation of soil; and carbon sequestration [9,10]. Animal manures impact the nutrient recovery of crops due to their more variable compositions and differential reaction rates compared to mineral fertilizers [11][12][13][14]. Nutrient recovery depends on a soil's capacity to supply nutrients and a plant's ability to acquire, transport, and remobilize nutrients [15].…”
Section: Introductionmentioning
confidence: 99%
“…nitrogen rate; ER, economic return; GS, growing season; N, nitrogen; Navailable, available winter cereal such as barley or triticale is subsequently sown as in other forage production 100 areas (Lloveras, 1987a(Lloveras, , 1987bMonaco et al, 2008;Trindade et al, 2001). Double-101 annual forage crop production is usually associated with dynamic livestock farming 102 where animals are fed with forages and their faeces, usually mixed with straw, are applied 103 to crops as fertilizer (Lloveras, 1987a;Perramon et al, 2016, Raphalen, 1980. Several 104 authors have reported studies of double-annual cropping systems with N organic 105 fertilization in Mediterranean environments (Grignani et al, 2007;Ovejero et al, 2016;106 Perramon et al, 2016;Yagüe and Quílez, 2010).…”
mentioning
confidence: 99%
“…The high NUEC and NAEC values for treatment 4·2 (Figure a,b) without additional yield increment (Table ) encouraged us to discard this treatment. Furthermore, the double‐cropping acts a buffer system for leaching when the total applied N does not exceed 330 kg N ha −1 , which is close to the critical N fertilization rate for N uptake in barley plus maize (137 + 146 kg N ha −1 respectively) found by Yagüe and Quilez () and close to the average of N maximum uptake of 648 kg N ha −1 (Perramon et al ., ) achieved at the highest productive rotation (2 years). The NUEC increases if this threshold is surpassed.…”
Section: Discussionmentioning
confidence: 52%